Changing patterns of religious affiliation, church attendance and marriage across five areas of Europe since the early 1980s: trends and associations - Williams, Emyr (Journal of beliefs and values, 2009)
This study draws on three waves of the European Values Survey (conducted between 1981 and 1984, between 1989 and 1993, and between 1999 and 2004) across five countries for which full data are available (Great Britain, Italy, the Netherlands, Northern Ireland, Spain, and Sweden) in order to address five research questions. Question one examined changes in religious affiliation. Across all five countries, the proportions of the non‐affiliated increased. Question two examined changes in church attendance. Across all five countries, the proportions of the non‐attenders increased. Question three examined changes in marital status. Across all five countries the proportions of the population checking the category ‘married’ declined, although in Spain the decline was marginal. Question four examined the association between religious affiliation and being married. The religious affiliated were more likely to be married than the non‐affiliated. Question five examined the association between church attendance and being married. Weekly attenders were more likely to be married than the non‐attenders. Overall these data support the close association between religion and marriage across five European countries (where there are very different religious climates) and support the hypothesis that changing religious values and changing family values go hand‐in‐hand.